Sex and age differences in head acceleration during purposeful soccer heading - Caccese, J. B.; Buckley, T. A.; Tierney, R. T.; Rose, W. C.; Glutting, J. J.; Kaminski, T. W. (Research in Sports Medicine, 2018)
Differences in head-neck segment mass, purposeful heading technique, and cervical strength and stiffness may contribute to differences in head accelerations across sex and age. The purpose of this study was to compare head acceleration across sex and age (youth [12-14 years old], high school and collegiate) during purposeful soccer heading. One-hundred soccer players (42 male, 58 female, 17.1 ± 3.5 years, 168.5 ± 20.3 cm, 61.5 ± 13.7 kg) completed 12 controlled soccer headers at an initial ball velocity of 11.2 m/s. Linear and rotational accelerations were measured using a triaxial accelerometer and gyroscope and were transformed to the head centre-of-mass. A MANOVA revealed a significant multivariate main effect for sex (Pillai`s Trace = .165, F(2,91) = 11.868, p < .001), but not for age (Pillai`s Trace = .033, F(4,182) = 0.646, p = .630). Peak linear and rotational accelerations were higher in females (40.9 ± 13.3 g; 3279 ± 1065 rad/s2) than males (27.6 ± 8.5 g, 2219 ± 823 rad/s2). These data suggest that under controlled soccer heading conditions, females may be exposed to higher head accelerations than males.